The Effect of Entrepreneurial Orientation, Market Orientation, Product Innovation on Business Performance - Fachrunisa, Diah; Oktarina, Nina; Kusumantoro, Kusumantoro (Journal of Economic Education, 2024)
Company performance is important matter for the company. This study aims to analyze the effect of entrepreneurial orientation, market orientation, and product innovation on micro-enterprise performance and is strengthened by competitive advantage. This study is quantitative research. The population in this study were 135 water hyacinth handicraft micro-entrepreneurs registered in the Semarang Regency Cooperatives and Small and Medium Enterprises Service. The sampling technique used was cluster proportional random sampling. The data processed in the study used primary data obtained from questionnaires distributed directly to water hyacinth handicraft micro-entrepreneurs in Semarang Regency. The data analysis methods used are descriptive analysis and Structural Equation Model (SEM) with the assistance of the SmartPLS 4.0 analysis tool. The result of this study shows that entrepreneurial orientation, market orientation, and product innovation have a positive and significant effect on the performance of micro-enterprises. Competitive advantage can moderate the effect of entrepreneurial orientation, market orientation, and product innovation on micro-enterprise performance. Suggestions for further research can add moderating variables that have never been studied, such as financial access and market orientation.